Regional effects of streptozotocin‐induced diabetes on shortening and calcium transport in epicardial and endocardial myocytes from rat left ventricle. Issue 22 (24th November 2016) - Smail, Manal M. A.; Qureshi, Muhammad A.; Shmygol, Anatoliy; Oz, Murat; Singh, Jaipaul; Sydorenko, Vadym; Arabi, Alya; Howarth, Frank C.; Al Kury, Lina
Abstract: In the heart, the left ventricle pumps blood at higher pressure than the right ventricle. Within the left ventricle, the electromechanical properties of ventricular cardiac myocytes vary transmurally and this may be related to the gradients of stress and strain experienced in vivo across the ventricular wall. Diabetes is also associated with alterations in hemodynamic function. The aim of this study was to investigate shortening and Ca 2+ transport in epicardial (EPI) and endocardial (ENDO) left ventricular myocytes in the streptozotocin (STZ)‐induced diabetic rat. Shortening, intracellular Ca 2+ and L‐type Ca 2+ current ( I Ca, L ) were measured by video detection, fura‐2 microfluorimetry, and whole‐cell patch clamp techniques, respectively. Time to peak (TPK) shortening was prolonged to similar extents in ENDO and EPI myocytes from STZ‐treated rats compared to ENDO and EPI myocytes from controls. Time to half (THALF) relaxation of shortening was prolonged in ENDO myocytes from STZ‐treated rats compared to ENDO controls. TPK Ca 2+ transient was prolonged in ENDO myocytes from STZ‐treated rats compared to ENDO controls. THALF decay of the Ca 2+ transient was prolonged in ENDO myocytes from STZ‐treated rats compared to ENDO controls. Sarcoplasmic reticulum (SR) fractional release of Ca 2+ was reduced in EPI myocytes from STZ‐treated rats compared to EPI controls. I C a, L activation, inactivation, and recovery from inactivation were not significantly altered in EPI and ENDO myocytes from STZ‐treated rats or controls. Regional differences in Ca 2+ transport may partly underlie differences in ventricular myocyte shortening across the wall of the healthy and the STZ‐treated rat left ventricle. Abstract : Results from this study suggest that transmural differences in calcium transport in the ventricular myocardium may underlie some of the disturbances in contractile properties of myocytes in diabetic heart.